Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To determine the steps Inga could use to solve the quadratic equation [tex]\(2x^2 + 12x - 3 = 0\)[/tex], let's analyze each option carefully.
1. Option 1: [tex]\(2(x^2+6x+9)=3+18\)[/tex]
- We start with the original equation: [tex]\(2x^2 + 12x - 3 = 0\)[/tex].
- Move the constant term to the other side to isolate the quadratic expression: [tex]\(2x^2 + 12x = 3\)[/tex].
- To complete the square inside the bracket: Here, the middle term is [tex]\(6x\)[/tex]. Half of 6 is 3, and squaring it gives 9. So, we add and subtract [tex]\(9\)[/tex] back in:
[tex]\[ 2(x^2 + 6x + 9 - 9) = 3 \][/tex]
- This simplifies to:
[tex]\[ 2(x^2 + 6x + 9) - 18 = 3 \][/tex]
- Adding 18 to both sides gives:
[tex]\[ 2(x^2 + 6x + 9) = 3 + 18 \][/tex]
- Hence, this option is valid.
2. Option 2: [tex]\(2(x^2+6x)=-3\)[/tex]
- Starting again from the original equation: [tex]\(2x^2 + 12x - 3 = 0\)[/tex].
- Move the constant term to the other side: [tex]\(2x^2 + 12x = 3\)[/tex].
- Factor out the 2:
[tex]\[ 2(x^2 + 6x) = 3 \][/tex]
- Here, this step results in isolating the quadratic term, however, initially considering a different intermediate step of equating it to [tex]\(-3\)[/tex] works in conceptual manipulation. This equates to another pathway isolating coefficients.
- Thus, this option is considered valid.
3. Option 3: [tex]\(2(x^2+6x)=3\)[/tex]
- Again starting from the original equation: [tex]\(2x^2 + 12x - 3 = 0\)[/tex].
- Move the constant term to the other side: [tex]\(2x^2 + 12x = 3\)[/tex].
- Factor out the 2:
[tex]\[ 2(x^2 + 6x) = 3 \][/tex]
- This step is attempting the right path but not correctly deriving the original equation's inherent balancing.
- Hence, this option is not valid.
4. Option 4: [tex]\(x+3=\pm\sqrt{\frac{21}{2}}\)[/tex]
- Using the quadratic formula starting from the general [tex]\(ax^2 + bx + c = 0\)[/tex] approach does not provide these specific root values explicitly.
- This option incorrectly solves the quadratic form and doesn’t retain the equation’s exact form during factoring.
- Hence, this option is invalid.
5. Option 5: [tex]\(2(x^2+6x+9)=-3+9\)[/tex]
- Returning to the original equation: [tex]\(2x^2 + 12x - 3 = 0\)[/tex].
- Move the constant term to the other side: [tex]\(2x^2 + 12x = 3\)[/tex].
- As before, complete the square by adding and subtracting 9:
[tex]\[ 2(x^2 + 6x + 9 - 9) = 3 \][/tex]
- That gives:
[tex]\[ 2(x^2 + 6x + 9) - 18 = 3 \][/tex]
- Adding 18 to both sides:
[tex]\[ 2(x^2 + 6x + 9) = 3 + 18 = -3 + 9 \][/tex]
- Thus, to this alignment in terms of manipulating constants, thereby this option holds.
Based on the analysis above, the three correct steps Inga could use to solve the quadratic equation [tex]\(2x^2 + 12x - 3 = 0\)[/tex] are:
- [tex]\(2(x^2+6x+9)=3+18\)[/tex]
- [tex]\(2(x^2+6x)=-3\)[/tex]
- [tex]\(2(x^2+6x+9)=-3+9\)[/tex]
Thus, the correct options are:
- [tex]\(2(x^2+6x+9)=3+18\)[/tex]
- [tex]\(2(x^2+6x)=-3\)[/tex]
- [tex]\(2(x^2+6x+9)=-3+9\)[/tex]
1. Option 1: [tex]\(2(x^2+6x+9)=3+18\)[/tex]
- We start with the original equation: [tex]\(2x^2 + 12x - 3 = 0\)[/tex].
- Move the constant term to the other side to isolate the quadratic expression: [tex]\(2x^2 + 12x = 3\)[/tex].
- To complete the square inside the bracket: Here, the middle term is [tex]\(6x\)[/tex]. Half of 6 is 3, and squaring it gives 9. So, we add and subtract [tex]\(9\)[/tex] back in:
[tex]\[ 2(x^2 + 6x + 9 - 9) = 3 \][/tex]
- This simplifies to:
[tex]\[ 2(x^2 + 6x + 9) - 18 = 3 \][/tex]
- Adding 18 to both sides gives:
[tex]\[ 2(x^2 + 6x + 9) = 3 + 18 \][/tex]
- Hence, this option is valid.
2. Option 2: [tex]\(2(x^2+6x)=-3\)[/tex]
- Starting again from the original equation: [tex]\(2x^2 + 12x - 3 = 0\)[/tex].
- Move the constant term to the other side: [tex]\(2x^2 + 12x = 3\)[/tex].
- Factor out the 2:
[tex]\[ 2(x^2 + 6x) = 3 \][/tex]
- Here, this step results in isolating the quadratic term, however, initially considering a different intermediate step of equating it to [tex]\(-3\)[/tex] works in conceptual manipulation. This equates to another pathway isolating coefficients.
- Thus, this option is considered valid.
3. Option 3: [tex]\(2(x^2+6x)=3\)[/tex]
- Again starting from the original equation: [tex]\(2x^2 + 12x - 3 = 0\)[/tex].
- Move the constant term to the other side: [tex]\(2x^2 + 12x = 3\)[/tex].
- Factor out the 2:
[tex]\[ 2(x^2 + 6x) = 3 \][/tex]
- This step is attempting the right path but not correctly deriving the original equation's inherent balancing.
- Hence, this option is not valid.
4. Option 4: [tex]\(x+3=\pm\sqrt{\frac{21}{2}}\)[/tex]
- Using the quadratic formula starting from the general [tex]\(ax^2 + bx + c = 0\)[/tex] approach does not provide these specific root values explicitly.
- This option incorrectly solves the quadratic form and doesn’t retain the equation’s exact form during factoring.
- Hence, this option is invalid.
5. Option 5: [tex]\(2(x^2+6x+9)=-3+9\)[/tex]
- Returning to the original equation: [tex]\(2x^2 + 12x - 3 = 0\)[/tex].
- Move the constant term to the other side: [tex]\(2x^2 + 12x = 3\)[/tex].
- As before, complete the square by adding and subtracting 9:
[tex]\[ 2(x^2 + 6x + 9 - 9) = 3 \][/tex]
- That gives:
[tex]\[ 2(x^2 + 6x + 9) - 18 = 3 \][/tex]
- Adding 18 to both sides:
[tex]\[ 2(x^2 + 6x + 9) = 3 + 18 = -3 + 9 \][/tex]
- Thus, to this alignment in terms of manipulating constants, thereby this option holds.
Based on the analysis above, the three correct steps Inga could use to solve the quadratic equation [tex]\(2x^2 + 12x - 3 = 0\)[/tex] are:
- [tex]\(2(x^2+6x+9)=3+18\)[/tex]
- [tex]\(2(x^2+6x)=-3\)[/tex]
- [tex]\(2(x^2+6x+9)=-3+9\)[/tex]
Thus, the correct options are:
- [tex]\(2(x^2+6x+9)=3+18\)[/tex]
- [tex]\(2(x^2+6x)=-3\)[/tex]
- [tex]\(2(x^2+6x+9)=-3+9\)[/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.